Impact of a novel, antimicrobial dressing on in vivo, Pseudomonas aeruginosa wound biofilm: Quantitative comparative analysis using a rabbit ear model. Issue 6 (8th January 2015) - Seth, Akhil K.; Zhong, Aimei; Nguyen, Khang T.; Hong, Seok J.; Leung, Kai P.; Galiano, Robert D.; Mustoe, Thomas A.
Abstract The importance of bacterial biofilms to chronic wound pathogenesis is well established. Different treatment modalities, including topical dressings, have yet to show consistent efficacy against wound biofilm. This study evaluates the impact of a novel, antimicrobial Test Dressing on Pseudomonas aeruginosa biofilm‐infected wounds. Six‐mm dermal punch wounds in rabbit ears were inoculated with 106 colony‐forming units of P. aeruginosa. Biofilm was established in vivo using our published model. Dressing changes were performed every other day with either Active Control or Test Dressings. Treated and untreated wounds were harvested for several quantitative endpoints. Confirmatory studies were performed to measure treatment impact on in vitro P. aeruginosa and in vivo polybacterial wounds containing P. aeruginosa and Staphylococcus aureus. The Test Dressing consistently decreased P. aeruginosa bacterial counts, and improved wound healing relative to Inactive Vehicle and Active Control wounds (p < 0.05). In vitro bacterial counts were also significantly reduced following Test Dressing therapy (p < 0.05). Similarly, improvements in bacterial burden and wound healing were also achieved in polybacterial wounds (p < 0.05). This study represents the first quantifiable and consistent in vivo evidence of a topical antimicrobial dressing's impact against established wound biofilm. The development of clinically applicable therapies against biofilm such as this is critical to improving chronic wound care.